EVALUASI DAN REKOMENDASI SISTEM MANAJEMEN KINERJA DI PT. XYZ - Lia Indriyati (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2016)
This study uses a qualitative thinking framework, in which researchers conduct an analysis of the performance management program implemented by PT. XYZ. Although aware that the importance of a good performance management system in an effort to develop its employees, but PT. XYZ conducts Performance Assessment activities as a one time event rather than an activity that is part of a continuous cycle series in a performance management system. So the results of the assessment did not provide an overview of employee performance during the period specified. The results of the analysis were: 1) No goal setting is contained in the performance contract process 2) There is no Coaching Counseling from the boss who is in the coaching phase 3) Performance Appraisal results are not used to identify training needs and employee development. Therefore, the author recommend some alternatives performance management program solutions that run as a continuous cycle, so the results will be useful not only for one interest only.Keywords: Work Motivation, Performance Management System, Performance Appraisal, Coaching Counseling.